The Management of Historical, Cultural, and Natural Heritage in the Master Plan of Vitória (ES, Brazil) - Mendes , Maressa Correa Pereira; Pasquotto, Geise Brizotti; Salcedo , Rosio Fernandes Baca (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze how the Master Plan of Vitória (PDU – Law nº 9.271/2018) incorporates provisions related to the preservation of cultural and natural heritage, verifying its alignment with national and international legislation as well as with the contemporary demands of the city. Methodology – The research adopted a qualitative approach, based on a literature review on cultural heritage and urban planning, as well as a documentary analysis of Law nº 9.271/2018. Analytical elements such as heritage listing, protection zones, land use, transport and road system, and urban furniture were defined and applied to the reading of the Master Plan’s articles. Originality/relevance – The study is situated within the debate on the integration between heritage and urban planning, exploring the existing gap in the practical application of legal guidelines in municipal master plans. It highlights academic relevance by discussing how regulatory instruments can contribute to the effective safeguarding of heritage in urban contexts undergoing transformation. Results – The findings point to significant advances in Vitória’s Master Plan, such as the creation of municipal inventories and heritage registers, protection zones, height and volume control, and the possibility of transferring development rights for listed properties. However, weaknesses were also identified, such as permissiveness in land uses that negatively affect the Historic Center and the absence of clearer strategies for sustainable mobility and the enhancement of public spaces. Theoretical/methodological contributions – The research reinforces the importance of critical analyses of master plans as instruments of integrated heritage management, contributing methodologically with analytical parameters that can be replicated in other urban contexts. Social and environmental contributions – The study highlights the role of heritage as an element of identity, social cohesion, and environmental quality in urban spaces. It also emphasizes the need for more consistent public policies to promote sustainability and socio-spatial vitality in historic centers.